Measuring financial satisfaction of Indonesian young adults: A SEM-PLS analysis - Farizka Shafa Nabila; Mahendra: Fakhri; Mahir Pradana; Budi Rustandi Kartawinata; Anita Silvianita (Journal of Innovation and Entrepreneurship, 2023)
People in Indonesia, particularly members of Generation Z, frequently struggle to manage their financial situation both now and in the future. The problem is brought on by a lack of understanding of financial investments. The purpose of this study is to ascertain the financial standing of Generation Z. A questionnaire with 100 respondents was employed in this investigation. In this study, financial attitudes serve as the independent variable, financial management serves as the intervention variable, and financial satisfaction serves as the dependent variable. A Likert scale was utilized as the measurement in the quantitative research technique. In this work, structural equation modeling (SEM) and SmartPLS software were utilized to process the data. The financial attitude variable has a positive and significant impact on financial happiness that is mediated by financial management. We also offer some recommendations and future research directions related to this topic.
Keywords: 650; Financial attitude; Financial management; Financial satisfaction